FAKTOR –FAKTOR YANG MEMPENGARUHI KEPATUHAN PAJAK WAJIB PAJAK ORANG PRIBADI (Studi Pada Wajib Pajak Orang Pribadi yang terdaftar di KPP Kebayoran Baru Tiga) - Fibria Anggraini P.L; Waluyo Waluyo (Jurnal Magister Akuntansi Trisakti, 2014)
The purpose of this study was to analyze the factors that affect tax compliance (tax compliance) individual taxpayers in the KPP Kebayoran Baru Tiga, South Jakarta. This study used a questionnaire survey design as an instrument. Respondents in this study were 85 individual taxpayers entrepreneur tax register at least one year and to submit the SPT.This study uses the variable individual behavior, motivation and organizational climate as the independent variable and tax compliance individual taxpayers as the dependent variable. Data analysis was performed using multiple linear regression analysis with SPSS for Windows Version 19.00. The results of this study indicate that individual behavior, motivation and organizational climate have significant effect on tax compliance individual taxpayers .